Adjuvant-Associated Peripheral Blood mRNA Profiles and Kinetics Induced by the Adjuvanted Recombinant Protein Candidate Tuberculosis Vaccine M72/AS01 in Bacillus Calmette–Guérin-Vaccinated Adults - van den Berg, Robert A.; De Mot, Laurane; Leroux-Roels, Geert; Bechtold, Viviane; Clement, Frédéric; Coccia, Margherita; Jongert, Erik; Evans, Thomas G.; Gillard, Paul; van der Most, Robbert G. (Frontiers in Immunology, 2018)
Systems biology has the potential to identify gene signatures associated with vaccine immunogenicity and protective efficacy. The main objective of this study was to identify optimal post-vaccination time points for evaluating peripheral-blood RNA-expression profiles in relation to vaccine immunogenicity and potential efficacy in recipients of the candidate tuberculosis vaccine M72/AS01. In this phase II open-label study (NCT01669096; https://clinicaltrials.gov/), healthy Bacillus Calmette-Guérin (BCG) primed, HIV-negative adults were administered two doses (30-days apart) of M72/AS01. Twenty subjects completed the study and 18 subjects received two doses. Blood samples were collected pre-dose 1, pre-dose 2 and 1, 7, 10, 14, 17 and 30 days post-dose 2. RNA expression in whole blood and peripheral-blood mononuclear cells (PBMCs) was quantified using microarray technology. Serum IFNG responses and M72-specific CD4+ T cell responses to vaccination, and the observed safety profile were similar to previous trials. Two different approaches were utilized to analyse the RNA expression data. First, a kinetic analysis of RNA expression changes using Blood Transcriptional Modules revealed early (1 day post dose-2) activation of several pathways related to innate immune activation, both in whole blood and PBMC. Second, using a previously identified gene signature as a classifier, optimal post-vaccination time points were identified. Since M72/AS01 efficacy remains to be established, a PBMC-derived gene signature associated with the protective efficacy of a similarly adjuvanted candidate malaria vaccine was used as a proxy for this purpose. This approach was based on the assumption that the AS01 adjuvant used in both studies could induce shared innate immune pathways. Subjects were classified as gene-signature positive or gene-signature negative. Assignments of subjects to gene-signature positive or gene-signature negative groups were confirmed by significant differences in RNA expression of the gene-signature genes in PBMCs at 14 days post-dose 2 relative to pre-vaccination and in whole-blood samples at 7, 10, 14 and 17 days post-dose 2 relative to pre-vaccination. Hence, in comparison with a pre-vaccination, 7, 10, 14, and 17 days post-vaccination appeared to be suitable time points for identifying potentially clinically relevant transcriptome responses to M72/AS01 in whole blood samples.